A method for constructing an optimal estimate calculation algorithm - Dokukin, A. A. (Computational mathematics and mathematical physics, 2006)
The problem of searching for an optimal procedure for constructing the best (in a certain sense) algorithm in the family of estimate calculation algorithms is considered. Such a procedure is designed, and upper bounds for its complexity are derived. The case of a two-dimensional feature space is analyzed in detail.[PUBLICATION ABSTRACT]